Les enjeux des discours de débat dans les médias - Marcel Burger (Communication)
This article looks at a particular form of style debates in electronic media : spectacle-debates. Although they advertise a pretension for general civic interest, these debates aim, above all else, to entertain and make loyal listeners and television viewers who are viewed as information consumers. In this sense, the spectacle-debates satisfy the commercial aims of information media which further value the civil aim instigate reflection, even to educate listeners and viewers as citizens. From an emblematic case study of the genre (the French television show : Du fer dans les épinards), attention is paid to the behaviour and discourse of the host with the hypothesis that these function as one of the revelations of the workings and the evolution of media use of debates and the stakes involved.